2000
DOI: 10.1007/s005310000122
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene variations in Arctic shelf hydrology and sea-ice regime: evidence from north of the Lena Delta

Abstract: Diatom assemblage studies are used to interpret past changes in river runoff (salinity) and sea-ice regime in the vicinity of the vast Lena River delta, southern Laptev Sea shelf. On the basis of their distribution in surface sediments, the shelf region outside the strong influence of riverine waters is characterized by a dominance in sea-ice diatoms and other marine species. Their numbers increase steeply (>20%) within the area of drifting pack ice. In contrast, the marginal zone of the delta, where exceeding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 18 publications
(29 reference statements)
0
17
0
Order By: Relevance
“…In addition to previously published data of diatom assemblage records in surface sediments from the Siberian arctic seas (Polyakova, 1994(Polyakova, , 1997Cremer, 1999a,b), recent studies indicate that diatoms are a valuable proxy for reconstructing major hydrological parameters in the shallow arctic seas (e.g., summer surface-water salinity and sea-ice conditions), as well as sedimentation processes in the river-proximal shelf areas (Bauch and Polyakova, 2000;. Likewise, the prevalence of arctic water masses and riverine freshwater in the Kara and Laptev seas as well as the rather similar species composition of diatom assemblages in both seas (Cremer, 1999a,b; allow us to apply the relation between surface salinity and freshwater diatoms in coretop sediments from the Kara Sea to downcore diatom records from the southeastern Laptev Sea (Bauch and Polyakova, 2003).…”
Section: Diatomsmentioning
confidence: 94%
“…In addition to previously published data of diatom assemblage records in surface sediments from the Siberian arctic seas (Polyakova, 1994(Polyakova, , 1997Cremer, 1999a,b), recent studies indicate that diatoms are a valuable proxy for reconstructing major hydrological parameters in the shallow arctic seas (e.g., summer surface-water salinity and sea-ice conditions), as well as sedimentation processes in the river-proximal shelf areas (Bauch and Polyakova, 2000;. Likewise, the prevalence of arctic water masses and riverine freshwater in the Kara and Laptev seas as well as the rather similar species composition of diatom assemblages in both seas (Cremer, 1999a,b; allow us to apply the relation between surface salinity and freshwater diatoms in coretop sediments from the Kara Sea to downcore diatom records from the southeastern Laptev Sea (Bauch and Polyakova, 2003).…”
Section: Diatomsmentioning
confidence: 94%
“…Furthermore, a correlation between T. clarkei and Cyst of P. dalei is not observable. Bauch and Polyakova (2000) reconstructed freshwater discharge and sea-ice cover from a diatom record of the inner Laptev Shelf off the Lena delta. Diatom assemblages show some variability in the past 2800 cal.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Variable reservoir age corrections have been applied previously to radiocarbon datings from the Laptev Sea. Bauch (1999) corrected all datings for a 14 C reservoir effect of 400 yr, whereas Bauch and Polyakova (2000) used a reservoir age correction of 313 yr but did not provide data used for the calculation. Dating by AMS 14 C of five bivalve shells, which were collected in the early twentieth century before the nuclear trials had started, allowed calculation of a reservoir age of 370 ± 49 yr (Bauch et al, 2001, in press).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diatom assemblage studies from surface sediments have shown (Bauch and Polyakova, 2000) that the pack ice area is typically associated with enhanced abundance of sea-ice species, whereas the landfast ice zone is characteristical for abundant freshwater species. The two microwave images (top left) reveal quite contrasting distribution of sea-ice concentration (source: http:// iup.physik.uni-bremen.de:8084/amsr/amsre.html).…”
Section: The Siberian Shelf Seas As Sensitive Benvironmental Recorderqmentioning
confidence: 99%